The Role of Education Using the Transtheoretical Stages of Change Approach in Digital Substraction Angiography Patients: A Literature Review - Trionyta Debora; Dwight Mahaputra Marulitua Hutapea; Refi Ikhtiari (Jurnal Penelitian Perawat Profesional, 2025)
Effective health education is crucial to improving procedure outcomes and patient compliance. The Transtheoretical Stages of Change approach has been proven effective in changing health behaviour by tailoring interventions to the patient's psychological readiness. This literature review aims to analyse the role and effectiveness of health education integrated with the Transtheoretical Stages of Change approach in patients undergoing DSA procedures. Method: A literature review was conducted by searching electronic databases such as PubMed, Google Scholar, and ScienceDirect. The search was limited to publications from 2020 to 2025. Results: The review results indicate that the Stages of Change approach is effective in identifying patients' readiness levels. Patients in the precontemplation and contemplation stages require education to raise awareness, while patients in the preparation and action stages require practical information and support to maintain behaviour. Integration of TTM in pre-DSA education significantly reduces anxiety levels, improves compliance with pre-procedure instructions and increases patient satisfaction. Conclusion: Personalised health education using the Transtheoretical Stages of Change framework is a strategic and effective approach to preparing patients for DSA. This approach enables targeted education, thereby improving clinical outcomes and the overall patient experience.